2001
DOI: 10.1038/sj.bmt.1703181
|View full text |Cite
|
Sign up to set email alerts
|

High-dose carboplatin with etoposide in patients with recurrent thymoma: the Indiana University experience

Abstract: Summary:Thymoma is a chemotherapy-sensitive tumor with a 30-50% 5-year survival in previously untreated patients. Unfortunately, durable CRs with salvage chemotherapy are rarely observed. We initiated a phase II trial of high-dose carboplatin and etoposide in patients with relapsed thymoma or thymic carcinoma. All patients had progressive disease (PD) after initial or salvage chemotherapy, but were not cisplatin-refractory. PBSCs were mobilized using 10 g/kg/day G-CSF. Patients received carboplatin 700 mg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, another intensive chemotherapy, ETP -IFX -CDDP (VIP) supported by G-CSF, has also reported disappointingly low response rates and no better survival . Hanna et al (2001) reported five patients with prior chemotherapy treated with highdose chemotherapy and stem cell support, but concluded that no superiority to conventional therapy was evident. Taken together with our results, intensification of chemotherapy does not appear sufficiently promising for treating advanced thymoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, another intensive chemotherapy, ETP -IFX -CDDP (VIP) supported by G-CSF, has also reported disappointingly low response rates and no better survival . Hanna et al (2001) reported five patients with prior chemotherapy treated with highdose chemotherapy and stem cell support, but concluded that no superiority to conventional therapy was evident. Taken together with our results, intensification of chemotherapy does not appear sufficiently promising for treating advanced thymoma.…”
Section: Discussionmentioning
confidence: 99%
“…2;3;24 . Hanna et al 5 report that thymic carcinoma are chemotherapy-sensitive tumours with a 30-50 % 5-year survival.…”
Section: Discussionmentioning
confidence: 98%
“…5 Neuroendocrine tumours, also found in the thymus, arise from Kulchitsky cells and vary in malignant potential. The histopathological classification and anatomical staging of primary thymic tumours remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…While the strategy of high-dose chemotherapy with stem cell support was feasible and demonstrated acceptable toxicity, the number of patients treated in the Indiana University series was small (4 patients with recurrent thymoma and 1 with recurrent thymic carcinoma) and the outcomes were no better than those obtained with standard chemotherapy regimens [32].…”
Section: Second-line Treatment and Novel Agentsmentioning
confidence: 89%